Robust, Superelastic Hard Carbon with In Situ Ultrafine Crystals. (22nd October 2019) - Ding, Chenfeng; Huang, Lingbo; Yan, Xiaodong; Dunne, Francis; Hong, Song; Lan, Jinle; Yu, Yunhua; Zhong, Wei‐Hong; Yang, Xiaoping
Abstract: Advancement in developing superelastic carbon aerogels is highly demanded in new industry sectors, particularly in wearable functional electronics for artificial intelligence applications. However, it is very challenging to increase the compressive strength and electrical conductivity while lowering the density of carbon aerogels. Here, an ultralight and superelastic hard carbon aerogel with in situ ultrafine carbon crystals is reported. Based on a novel precursor prepared from self‐assembling bacterial cellulose and thiourea molecules, the resulting aerogel possesses a unique cellular structure and simultaneously exhibits remarkable compressive and electrical properties with ultralow density in addition to excellent compressive cyclability. Specifically, the normalized compression strength and electrical conductivity are up to 20 and 10 times, respectively, of reported carbon aerogels. Armed with the compressed aerogel electrodes, the supercapacitor exhibits excellent electrochemical performance in areal capacitance, rate capability, and high‐power cyclic stability. Furthermore, the supercapacitor displays distinguished pressure‐response capacitive signal and excellent signal cyclicality. This study provides a unique carbon aerogel for advanced wearable monitoring and energy storage systems. Abstract : An ultralight and superelastic hard carbon aerogel with in situ ultrafine crystals is reported. The aerogel exhibits remarkable normalized compression strength and superhigh normalized electrical conductivity in addition to excellent compressive cyclability. Armed with aerogel electrodes, the supercapacitor presents excellent areal capacitance and pressure‐response performance. This study provides a unique hard carbon for advanced wearable monitoring and energy storage systems.